BIMBINGAN DAN PELATIHAN PEMBUATAN BAKSO DAN NUGGET BAGI IBU-IBU DESA TORJUN SAMPANG MADURA - Nurbaya, Siti; Utomo, Heru; Suryanto, Bambang (Dharma: Jurnal Pengabdian Masyarakat, 2020)
Torjun village that located on the Sampang, Madura island was one of the village that very close to the beach. This village was also a fishing area because 95% of the population, especially men, lived by "majeng" (or as fishermen). Meanwhile, the wife of the fishermens was only became housewives. The problem that usually arises in fishermen's daily activities was the highly-needs for family life that wasn’t inapropriate with the income level from fishing, so that they must seeking any opportunities that could improve their income. Therefore, they was also needs special skills that can increase income for fishermen's wives. From that problems, we will give a training in making meatballs and nuggets from fish. This activity also received a high enthusiasm from the participants. This enthusiasm was proven by the completeness of the 20 participants that were listened to the discussion. All of participants were active from the beginning until the end of the section. As the PKM groups, we were concluded that all participants were able to practice the results of the training by being able to made fish balls and fish nuggets that made from tuna and mackerel fish.